2022
DOI: 10.1371/journal.pgph.0000378
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and trend of TB/HIV co-infection in Suhum Municipality, Ghana

Abstract: Tuberculosis (TB) and Human Immunodeficiency Virus (HIV) infections have been identified to form a deadly synergy that is posing serious threats to human health and economic development particularly in Sub-Saharan Africa (SSA). Six years into the end TB strategy, it is imperative to assess HIV detection rate among TB patients in order to determine the prevalence as well as establish the temporal trend of the co-morbidity in the Eastern region of Ghana where the magnitude of HIV and TB/HIV co-morbidity have con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
1
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 22 publications
0
3
1
1
Order By: Relevance
“…In the current study, the TB prevalence among HIV seropositives was 38.5%. This finding is higher than the study conducted in Nepal, which reported 9.9% [23], the study done in Ghana, which reported 18.6% [24], Debre Markos Referral Hospital, Ethiopia, which reported 16.6% [25], and Addis Ababa, which reported 5.3% [26]. However, this finding is lower than the study conducted in Tanzania, which reported 58.3% [27], and Bale Goba and Robe hospitals, which reported 44.4% [20].The implications are that TB is the most opportunistic infection among people living with HIV and increases the chance of latent TB infection progressing to active TB disease.…”
Section: Discussioncontrasting
confidence: 72%
“…In the current study, the TB prevalence among HIV seropositives was 38.5%. This finding is higher than the study conducted in Nepal, which reported 9.9% [23], the study done in Ghana, which reported 18.6% [24], Debre Markos Referral Hospital, Ethiopia, which reported 16.6% [25], and Addis Ababa, which reported 5.3% [26]. However, this finding is lower than the study conducted in Tanzania, which reported 58.3% [27], and Bale Goba and Robe hospitals, which reported 44.4% [20].The implications are that TB is the most opportunistic infection among people living with HIV and increases the chance of latent TB infection progressing to active TB disease.…”
Section: Discussioncontrasting
confidence: 72%
“…Also, males have poor health-seeking behaviour than females in our part of the country which may adversely impact their treatment adherence and outcomes. Several studies have also reported the lethal synergy between TB and HIV [7,[27][28][29][30][31]. In congruence, Amante and Ahemed [32] and Teketelew et al [20] demonstrated that younger age and Pulmonary negative TB cases were at significant risk of survival.…”
Section: Discussionmentioning
confidence: 97%
“…As an example, a study carried out in a region of Ghana showed that the strengthening of collaborative actions between TB and HIV control programs, such as the provision of tests, resulted in significant periods of increased coinfection in the time series from 2008 to 2018. 22 …”
Section: Discussionmentioning
confidence: 99%
“…As an example, a study carried out in a region of Ghana showed that the strengthening of collaborative actions between TB and HIV control programs, such as the provision of tests, resulted in significant periods of increased coinfection in the time series from 2008 to 2018. 22 The dual testing policy is particularly relevant in Brazil, given the high number of people who discover their HIV infection only as a result of TB. In 2020, data resulting from linkage between the SINAN, SIM, SISCEL and SICLOM databases showed that 47.9% of registered coinfection cases were diagnosed with HIV due to TB.…”
Section: Original Articlementioning
confidence: 99%